Elevated content of p53 protein in the absence of p53 gene mutations as a possible prognostic marker for human renal cell tumors - Chemeris, Galina; Loktinov, Alexandre; Rempel, Annette; Schwarz, Michael; Bannasch, Peter (Virchows Archiv, 1995)
P53 tumour suppressor gene expression was estimated immunohistochemically using DO-1 monoclonal antibody (recognising both wild-type and mutant p53) in 88 human renal tumours. Single strand conformation polymorphism (SSCP) analysis of possible mutations within exons 4-8 of the p53 gene was performed in 29 of the tumours (mostly immunostaining-positive cases). Obviously elevated p53 content was detected with DO-1 antibody in chromophobic cell carcinomas and most clear/chromophilic cell tumours (in chromophilic cell populations). In contrast, clear cell carcinomas demonstrated either complete absence of p53 expression or the presence of single immunopositive nuclei. Oncocytomas were completely negative. Additional immunostaining of the positive samples with mutant p53-specific Pab240 monoclonal antibody failed to detect immunopositive material. No p53 mutation was found in any of the samples analysed by SSCP. Our results suggest that the elevated p53 content in human renal cell carcinomas does not result from gene mutation and that p53 gene alterations are probably not an important mechanism in the development of human renal cell carcinomas. Accumulation of the wild-type p53 protein may be a useful prognostic marker indicating neoplastic progression and malignancy.